Role of pKa in establishing the crystal structures of six hydrogen-bonded compounds of 4-methylquinoline with different isomers of chloro- and nitro-substituted benzoic acids - Hiroyuki Ishida (International Union of Crystallography, 2021)
The structures of the six hydrogen-bonded 1:1 compounds of 4-methylquinoline (C10H9N) with chloro- and nitro-substituted benzoic acids (C7H4ClNO4), namely, 4-methylquinolinium 2-chloro-4-nitrobenzoate, C10H10N+·C7H3ClNO4−, (I), 4-methylquinoline–2-chloro-5-nitrobenzoic acid (1/1), C10H9N·C7H4ClNO4, (II), 4-methylquinolinium 2-chloro-6-nitrobenzoate, C10H9.63N0.63+·C7H3.37ClNO40.63−, (III), 4-methylquinolinium 3-chloro-2-nitrobenzoate, C10H9.54N0.54+·C7H3.46ClNO40.54−, (IV), 4-methylquinolinium 4-chloro-2-nitrobenzoate, C10H10N+·C7H3ClNO4−, (V), and 4-methylquinolinium 5-chloro-2-nitrobenzoate, C10H10N+·C7H3ClNO4−, have been determined at 185–190 K. In each compound, the acid and base molecules are linked by a short hydrogen bond between a carboxy (or carboxylate) O atom and an N atom of the base. The O...N distances are 2.5652 (14), 2.556 (3), 2.5485 (13), 2.5364 (13), 2.5568 (13) and 2.5252 (11) Å, respectively, for compounds (I)–(VI). In the hydrogen-bonded acid–base units of (III) and (IV), the H atoms are each disordered over two positions with O site:N site occupancies of 0.37 (3):0.63 (3) and 0.46 (3):0.54 (4), respectively, for (III) and (IV). The H atoms in the hydrogen-bonded units of (I), (V) and (VI) are located at the N-atom site, while the H atom in (II) is located at the O-atom site. In all the crystals of (I)–(VI), π–π stacking interactions between the quinoline ring systems and C—H...O hydrogen bonds are observed. Similar layer structures are constructed in (IV)–(VI) through these interactions together with π–π interactions between the benzene rings of the adjacent acid molecules. A short Cl...Cl contact and an N—O...π interaction are present in (I), while a C—H...Cl hydrogen bond and a π–π interaction between the benzene ring of the acid molecule and the quinoline ring system in (II), and a C—H...π interaction in (III) are observed. Hirshfeld surfaces for the title compounds mapped over dnorm and shape index were generated to visualize the weak intermolecular interactions.